2014
DOI: 10.4049/jimmunol.1400769
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin Complex 1 Orchestrates Invariant NKT Cell Differentiation and Effector Function

Abstract: Invariant NKT (iNKT) cells play critical roles in bridging innate and adaptive immunity. The Raptor containing mTOR complex 1 (mTORC1) has been well documented to control peripheral CD4 or CD8 T cell effector or memory differentiation. However, the role of mTORC1 in iNKT cell development and function remains largely unknown. By using mice with T cell–restricted deletion of Raptor, we show that mTORC1 is selectively required for iNKT but not for conventional T cell development. Indeed, Raptor-deficient iNKT cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 41 publications
3
52
0
Order By: Relevance
“…Of note, NKT thymocytes, unlike conventional T cells, undergo blasting and cell division during thymic development (1, 2). Consistent with this notion, loss of mTORC1 activity by deletion of Raptor has been shown in very recent studies to block development of iNKT cells at early stage and impair their functionality (16, 17), while permitting the normal development of conventional T cells. However, the role of mTOR in lineage diversification of iNKT cells is less clear (18).…”
Section: Introductionsupporting
confidence: 54%
“…Of note, NKT thymocytes, unlike conventional T cells, undergo blasting and cell division during thymic development (1, 2). Consistent with this notion, loss of mTORC1 activity by deletion of Raptor has been shown in very recent studies to block development of iNKT cells at early stage and impair their functionality (16, 17), while permitting the normal development of conventional T cells. However, the role of mTOR in lineage diversification of iNKT cells is less clear (18).…”
Section: Introductionsupporting
confidence: 54%
“…We showed that autophagy deficiency led to hyperactivity of mTORC1 and mTORC2 in i NKT cells. The T cell specific deletion of Raptor, an essential component of mTORC1, also impaired the maturation of i NKT cells (70), suggesting the need for a balance, with either too much or too little mTORC1 inhibiting i NKT cell development.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ablation of mTORC1 signaling also causes a severe early defect in iNKT cell development (58,59). We speculate that iNKT cells undergo an early glycolytic shift driven by c-myc, but at the end of their expansion phase they have to be able to enter a quiescent, less metabolically active phase that relies on fatty acids, amino acids, and glucose as energy sources (60).…”
Section: Discussionmentioning
confidence: 99%